Predictors of Parental Accommodation and Response Treatment in Young Children With Obsessive-Compulsive Disorder - Rosa-Alcázar, Ángel; Rosa-Alcázar, Ana I.; Parada-Navas, José Luis; Olivares-Olivares, Pablo J.; Rosa-Alcázar, Encarnación (Frontiers in Psychiatry, 2021)
Background: Cognitive–behavioral family-based treatment (CBFT) is the treatment standard in very young children with obsessive–compulsive disorder (OCD), which includes the same core components of cognitive–behavioral therapy (CBT) with significant family involvement. Although the latter reports high rates of remission, some children do not improve with treatments. Therefore, it is necessary to identify possible moderating variables such as comorbidity, severity of disorder, years of onset, parental anxiety, and parental accommodation. This study has two main aims: (1) to propose a predictive model on family accommodation (father and mother), taking into account variables related to the children (severity of obsessive–compulsive responses, internalizing and externalizing symptoms, and comorbidity) and with the parents before intervention (worry, accommodation of one parental member over the other) and (2) to examine the mediating role of externalizing symptoms and mother's accommodation in the relation between initial severity and improvement of severity of obsessive–compulsive responses in children aged 5–8 years. Methods: Participants comprised 56 children with OCD [mean = 6.61 (SD = 0.76)] and their parents; 79% of the sample was men. Treatment was implemented by two clinicians specialized in OCD (>15 years of experience). Clinicians were trained to administer CBT protocol in the same way. They were doctors of clinical psychology and researchers at the OCD. Results: Mother's accommodation was associated with child variables (Child Behavior Checklist–Externalizing and Initial Severity, Children's Yale–Brown Obsessive–Compulsive Scale). Father's accommodation could be explained by parent variables (mother's accommodation and worry). Simple mediation model tested using the SPSS macro PROCESS supported the relation of the initial severity of symptoms with that following intervention, through the simple indirect effect of externalizing symptoms of the child. Conclusions: Comorbidities with externalizing symptoms, father's worry, and mother's accommodation were variables that should be controlled in treatment of pediatric OCD.